Acute podocyte injury is not a stimulus for podocytes to migrate along the glomerular basement membrane in zebrafish larvae - Siegerist, Florian (Sci Rep, 2017)
Podocytes have a unique 3D structure of major and interdigitating foot processes which is the prerequisite for renal blood filtration. Loss of podocytes leads to chronic kidney disease ending in end stage renal disease. Until now, the question if podocytes can be replaced by immigration of cells along the glomerular basement membrane (GBM) is under debate. We recently showed that in contrast to former theories, podocytes are stationary in the zebrafish pronephros and neither migrate nor change their branching pattern of major processes over 23 hours. However, it was still unclear whether podocytes are able to migrate during acute injury. To investigate this, we applied the nitroreductase/metronidazole zebrafish model of podocyte injury to in vivo two-photon microscopy. The application of metronidazole led to retractions of major processes associated with a reduced expression of podocyte-specific proteins and a formation of subpodocyte pseudocyst. Electron microscopy showed that broad areas of the capillaries became denuded. By 4D in vivo observation of single podocytes, we could show that the remaining podocytes did not walk along GBM during 24 h. This in vivo study reveals that podocytes are very stationary cells making regenerative processes by podocyte walking along the GBM very unlikely.